Al-Ghazali’s Patience Therapy in Reducing Students’ Career Anxiety - Najwa, Hilwatun; Albaar, Ragwan (Proceedings Of International Conference On Islamic Counseling Studies (ICONICS), 2025)
This study examines Al-Ghazali’s concept of patience therapy as an approach to reducing career anxiety among students who work while pursuing higher education. Working students often face multiple pressures, including academic demands, economic challenges, limited support, and varying levels of self-adjustment, all of which contribute to heightened anxiety. Using a qualitative descriptive method supported by interviews and literature review, this research explores how Al-Ghazali’s teachings particularly the practices of self-control, acceptance of destiny, dhikr, and inner purification provide both psychological and spiritual mechanisms for managing anxiety. The findings show that patience therapy fosters emotional stability, enhances self-regulation, and strengthens personal resilience. Through the integration of spiritual reflection and behavioral discipline, students are better able to balance academic and work responsibilities, resulting in reduced career anxiety and improved well-being. This study highlights the relevance of classical Islamic thought as a holistic coping strategy for contemporary mental health issues among working students.